Cam Jansen and the chocolate fudge mystery - Adler, David A.; Natti, Susanna (New York, N.Y., U.S.A. : Viking, 1993)
When Cam Jansen and her friend Eric uncover a mystery while selling fudge door-to-door to raise money for the local library, Cam uses her photographic memory to foil a crime.
"Ages 7-10"--cover p. [4].
560
Keywords: Mystery fiction